Vamos começar pelo fim?: a pedagogia cemiterial como projeto educativo no espaço escolar - Rigo, Kate Fabiani (2015)
The goal of this dissertation is to present the Cemeterial Pedagogy as a proposal for action to be developed in primary education. The methodology chosen is founded on the meta-analysis of data from the 2010 Census, regarding the religious profile of Brazilian adolescents and on the virtual ethnographic research, through the monitoring of Community Facebook pages connected to the encouragement and extinction of self-injurious and suicidal behavior among Brazilian adolescents ages 13 to 17. The structure was divided into four distinct chapters. The first presents the individual, in the adolescent phase, based on the bio-ecological model of Bronfenbrenner and how this adolescent inserts him/herself in the faith stages and the Google God. The second verifies the perception of death and dying of the virtualized adolescent as well as his or her interaction with Community Facebook pages associated to the encouragement and extinction of self-injurious behavior. The third analyzes the importance of Religious Education as a curricular component that is compatible to the development of the theme of death and dying in the school space through the Cemeterial Pedagogy. Finally, the last chapter proposes a model of action for the application of the Cemeterial Pedagogy with adolescents in the school space.